Modern Microsurgical Operations of Chronic Purulent Otitis Media - Khushvakova Nilufar Jurakulovna; Raxmonkulov Umedjon Alisher oʻgʻli; Moʻminov Akbarali Ikrom oʻgʻli; Norpulatov Kurbonali Baxriddin oʻgʻli; Samandarov Davron Farxodovich (Journal of Science in Medicine and Life, 2024)
Relevance of the problem: The operation is performed for the surgical treatment of otosclerosis and tympanosclerosis. The operation is performed under anesthesia. The essence of the operation is the use of intraocular access using a Carl Zeiss operating microscope (Germany). During the intervention, the eardrum is raised, the fixed stapes is removed and replaced with a prosthesis. Stapes prosthesis is performed in two ways: with Teflon prosthesis (Shea technique) or wire-oil prosthesis (Schukneht technique) implantation. In the second case, part of the fat is removed from the patient's ear cavity. About 30 operations are performed a year. The average length of hospital stay is 12 days. Recovery occurs within 1-2 months. Complications: complete deafness in the operated ear develops in 2-3% of patients, which corresponds to world statistics. Dispensary surveillance is carried out at the place of residence.